2022
DOI: 10.1507/endocrj.ej21-0584
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain-derived neurotrophic factor in the serum of persons with nonalcoholic fatty liver disease

Abstract: The increasing prevalence of nonalcoholic fatty liver disease (NAFLD) is a global health problem. In recent years, the inhibitory effect of brain-derived neurotrophic factor (BDNF) on diabetes mellitus and fatty liver has been clarified. The purpose of this study was to analyze the relationship between serum BDNF and NAFLD which caused by abnormal metabolism of glucose and lipids. This cross-sectional study involved 429 participants (mean age, 63.5 years: men, 38.5%) with low alcohol intake. Of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, BDNF has been proposed to act as a connection between the central nervous system and peripheral organs through regulating energy intake and expenditure and to exert pleiotropic effects in the periphery beyond the central nervous system [36,42]. In a cross-sectional study, Hattori et al recently reported high levels of serum BDNF in NAFLD [43]. The authors of that study speculated that the elevation of serum BDNF levels might be a compensatory response aimed at counteracting abnormal glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BDNF has been proposed to act as a connection between the central nervous system and peripheral organs through regulating energy intake and expenditure and to exert pleiotropic effects in the periphery beyond the central nervous system [36,42]. In a cross-sectional study, Hattori et al recently reported high levels of serum BDNF in NAFLD [43]. The authors of that study speculated that the elevation of serum BDNF levels might be a compensatory response aimed at counteracting abnormal glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 165 ] found that BDNF expression appears to require activity of the MyD88/NF- κ B signaling pathway to induce innate immune responses which also induces innate immune responses [ 165 ]. BDNF is an important marker for preventing and treating NAFLD [ 166 ], as its serum level has positive association with NAFLD [ 167 ]. However, no in vitro or in vivo experiments have found the signaling pathway between BNDF and NAFLD.…”
Section: Myokines and Nf- κ B Activationmentioning
confidence: 99%